2018
DOI: 10.1016/j.hal.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Brevetoxin (PbTx-2) influences the redox status and NPQ of Karenia brevis by way of thioredoxin reductase

Abstract: The Florida red tide dinoflagellate, Karenia brevis, is the major harmful algal bloom dinoflagellate of the Gulf of Mexico and plays a destructive role in the region. Blooms of K. brevis can produce brevetoxins: ladder-shaped polyether (LSP) compounds, which can lead to adverse human health effects, such as reduced respiratory function through inhalation exposure, or neurotoxic shellfish poisoning through consumption of contaminated shellfish. The endogenous role of the brevetoxins remains uncertain. Recent wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Another proposed role for a toxin is mediating redox potential by brevetoxin in the chloroplast of Karenia brevis . 90 This helps explain why complex polyketides are found in photosynthetic species as well as the apparent association between function and synthesis in the chloroplast since it is a major source of redox stress. Thus, focusing on “toxin” synthesis may not be advantageous in the long run versus understanding the modular synthases in dinoflagellates as a whole and their biological role within dinoflagellates.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed role for a toxin is mediating redox potential by brevetoxin in the chloroplast of Karenia brevis . 90 This helps explain why complex polyketides are found in photosynthetic species as well as the apparent association between function and synthesis in the chloroplast since it is a major source of redox stress. Thus, focusing on “toxin” synthesis may not be advantageous in the long run versus understanding the modular synthases in dinoflagellates as a whole and their biological role within dinoflagellates.…”
Section: Discussionmentioning
confidence: 99%
“…If this were true, then strains that differ in cellular toxin loads should have observable differences in biochemical parameters related to redox status, and this is indeed the case. Low toxin producing K. brevis has been consistently shown to have higher cellular thiol content including a higher level of reduced cysteine in the proteome when compared to a high toxin producing strain . Recently reported redox proteomics studies using cysteine reactive tandem mass tags have identified significant differences in the redox status of the proteomes of high and low toxin strains of K. brevis with the high toxin proteome in a more oxidized state .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that this is a mechanism of allelopathy for K. brevis , by interfering with redox regulation of algal competitors that lack a mechanism to compensate for the inhibition of TrxR. It is perhaps noteworthy that several different homologues of NADPH-dependent TrxR have been identified in the K. brevis transcriptome library, possibly a result of the complex evolutionary origins of the K. brevis chloroplast . These homologues may differ in sensitivity to PbTx-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some algae species, including Ptychodiscus brevis , produce BTX-2 (brevetoxin B) which results in neurotoxic shellfish poisoning (NSP) by consuming BTX-2 contaminated shellfish [ 157 , 158 ]. To detect brevetoxin B (BTX-2) in seafood, Tang et al devised a practicable and straightforward magneto-controlled immunosensing platform.…”
Section: Food Toxicant Analyses Of 2d Nanomaterial-based Electrochmentioning
confidence: 99%